Reconstruction of Creative Products Based Using a Design Thinking Approach The “Spirit of Majapahit” Case Study - Shienny Megawati Sutanto; Marina Wardaya; Hutomo Setia Budi (Universitas Multimedia Nusantara, 2023)
Indonesia is a country rich in culture and heritage. This richness of culture can be seen from artifacts and historical sites found throughout Indonesia. However, Indonesia's younger generations are less familiar with their own culture. This is caused by various things, one of which is the rarity of historical heritage products reconstructed to be introduced to Indonesia's younger generation. This research was conducted to analyze the process of reconstructing Indonesian historical heritage, the Spirit of Majapahit using a Design Thinking approach. The research and analysis of the process of re-creating the Spirit of Majapahit can form the basis of a design mindset that can be used as a guide in recreating local Indonesian historical products. This research uses a qualitative data collection method which is carried out by structured interviews with personnel who are actively involved in the process of reinventing the Spirit of Majapahit and experts on Indonesian culture. In addition to qualitative methods, literature studies are conducted to find data regarding the process of creating creative products, previous research on the adaptation of Indonesian local historical products, and audience responses to the reconstruction of past cultural products. The results of the study are used as the basis for creating a product design mindset module based on Indonesian local history which is linked to a systematic and replicable Design Thinking approach. Keywords: design thinking; spirit of majapahit; history; cultural revitalization.